Effect of Different Nuclear Localization Signals on the Subcellular Localization and Anti-HIV-1 Function of the MxB Protein - Chai, Keli; Wang, Zhen; Pan, Qinghua; Tan, Juan; Qiao, Wentao; Liang, Chen (Frontiers in Microbiology, 2021)
Interferon exerts its antiviral activity by stimulating the expression of antiviral proteins. These interferon stimulate genes (ISGs) often target a group of viruses with unique molecular mechanisms. One such ISG is myxovirus resistance B (MxB) that has been reported to inhibit human immunodeficiency virus type 1 (HIV-1) by targeting viral capsid and impairing nuclear import of viral DNA. The antiviral specificity of MxB is determined by its N-terminal 25 amino acids sequence which has the nuclear localization activity, therefore functions as a nuclear localization signal (NLS). In this study, we report that the bipartite NLS, but not the classic NLS, the PY-NLS, nor the arginine-rich NLS, when used to replace the N-terminal sequence of MxB, drastically suppress HIV-1 gene expression and virus production, thus creates a new anti-HIV-1 mechanism. MxB preserves its anti-HIV-1 activity when its N-terminal sequence is replaced by the arginine-rich NLS. Interestingly, the arginine-rich NLS allows MxB to inhibit HIV-1 CA mutants that are otherwise resistant to wild type MxB, which suggests sequence specific targeting of viral capsid. Together, these data implicate that it is not the nuclear import function itself, but rather the sequence and the mechanism of action of the NLS which define the antiviral property of MxB.